High prevalence and functional effects of serum antineuronal antibodies in patients with gastrointestinal disorders. Issue 6 (18th January 2018) - Lütt, A.; Michel, K.; Krüger, D.; Volz, M. S.; Nassir, M.; Schulz, E.; Poralla, L.; Tangermann, P.; Bojarski, C.; Höltje, M.; Teegen, B.; Stöcker, W.; et al.
Abstract: Background: Antineuronal antibodies can be associated with both gastrointestinal (GI) and brain disorders. For example, antibodies against the potassium channel subunit dipeptidyl‐peptidase‐like protein‐6 (DPPX) bind to neurons in the central nervous system (CNS) and myenteric plexus and cause encephalitis, commonly preceded by severe unspecific GI symptoms. We therefore investigated the prevalence of antineuronal antibodies indicative of treatable autoimmune CNS etiologies in GI patients. Methods: Serum samples of 107 patients (Crohn's disease n = 42, ulcerative colitis n = 16, irritable bowel syndrome n = 13, others n = 36) and 44 healthy controls were screened for anti‐DPPX and further antineuronal antibodies using immunofluorescence on rat brain and intestine and cell‐based assays. Functional effects of high‐titer reactive sera were assessed in organ bath and Ussing chamber experiments and compared to non‐reactive patient sera. Key Results: Twenty‐one of 107 patients (19.6%) had antibodies against the enteric nervous system, and 22 (20.6%) had anti‐CNS antibodies, thus significantly exceeding frequencies in healthy controls (4.5% each). Screening on cell‐based assays excluded established antienteric antibodies. Antibody‐positive sera were not associated with motility effects in organ bath experiments. However, they induced significant, tetrodotoxin (TTX)‐insensitive secretion in Ussing chambers compared to antibody‐negative sera. Conclusions & Inferences: Antineuronal antibodies were significantly more frequent in GI patients and associated with functional effects on bowel secretion. Future studies will determine whether such antibodies indicate patients who might benefit from additional antibody‐directed therapies. However, well‐characterized encephalitis‐related autoantibodies such as against DPPX were not detected, underlining their rarity in routine cohorts. Abstract : In this study, we examined the frequency and functional effects of antineuronal antibodies in gastrointestinal patients. Antineuronal autoantibodies were significantly more frequent in patients than in healthy controls. Furthermore, antibody‐positive sera showed a significant effect on intestinal secretion.